Les rôles exercés par des enseignantes atikamekw à l’éducation préscolaire en contexte de jeu symbolique pour favoriser l’émergence de l’écrit - Jacob, Elisabeth; Charron, Annie (Canadian Journal of Education/Revue canadienne de l’éducation, 2019)
In this article, the aim is to analyze Atikamekw preschool teachers’s roles in the context of pretend play to promote emergent literacy. These preschool teachers are responsible for developing emergent literacy skills for children in atikamekw language. One of the ways this can be done is to encourage pretend play. Collaborative research, the methodological approach used, allowed the teachers to adopt five roles: storyteller, guide, informant, mediator and decision-maker. These roles take into account the cultural and sociolinguistic context of the relevant indigenous community. Keywords: teachers’ roles, pretend play, emergence of literacy, collaborative research, preschool